Strengthening Santri Communication Competence through Khitobiyah Activities at Miftahul Huda Islamic Boarding School - Santi Ratnawati; Kamalun Ni’am; Aliwan; M. Arief Hidayatulloh; Choirul Anam; Abdul Hakim (Journal of Communication Studies, 2025)
This study aims to describe the implementation of khitobiyah activities, identify the communication competencies developed, and analyze their role in strengthening the communication competence of santri at Miftahul Huda Islamic Boarding School, Ngroto, Gubug, Grobogan. The study employed a qualitative approach with a case study design. Data sources included the boarding school leader, supervising teachers, and santri who actively participated in khitobiyah activities. Data were collected through observation, in-depth interviews, and documentation. Data analysis followed the Miles, Huberman, and Saldaña model, consisting of data reduction, data display, and conclusion drawing. Data validity was ensured through source and technique triangulation. The findings reveal that khitobiyah activities are implemented systematically through the stages of material preparation, speech delivery, and regular evaluation. The communication competencies developed include verbal, nonverbal, interpersonal, and psychological aspects. Santri demonstrated improvements in organizing and delivering materials systematically, using intonation, facial expressions, eye contact, and gestures more effectively, as well as increased self-confidence and courage in public speaking. Khitobiyah activities play a significant role in strengthening communication competence through habituation, practical experience, social interaction, and continuous evaluation. The study concludes that khitobiyah serves as a communication learning model based on pesantren culture that holistically integrates communication knowledge, skills, motivation, and attitudes.